PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM ORGANISASI TERHADAP KINERJA GURU DENGAN MODERASI KOMITMEN ORGANISASI - Edi Muryanto, 11.52.02.0033 (Students Journal of Economic and Management, 2013)
This aim of this study to identify and examine the influence of principal leadership, organizational climate of teachers performance in junior high school by using moderation comitment organizational, the object of this study is SMP teachers in Kudus regency. The technique of sampling used Proportional Random Sampling. From the results of the Proportional random sampling are 229 teacchers as sample. The mechanical examination data used analysis factor of validity test,Â  reliability test by using Cronbach alpha formula, regression analysis, and significance test determination coefficient is used to prove the hypothesis and moderation test. The study showed that: variable organizational commitment gave good influence in moderating the principal leadership and organizational climate of teachers performance . The leadership of principal and organizational climate give positive and significant influence teachers performance. Keywords:Â  principal leadership, organizational climate, teachers performance and Organizational commitment